Polarization of Immune Cells in the Pathologic Response to Inhaled Particulates - Ma, Qiang (Frontiers in Immunology, 2020)
Polarization of immune cells is commonly observed in host responses associated with microbial immunity, inflammation, tumorigenesis, and tissue repair and fibrosis. In this process, immune cells adopt distinct programs and perform specialized functions in response to specific signals. Accumulating evidence indicates that inhalation of micro- and nano-sized particulates activates barrier immune programs in the lung in a time- and context-dependent manner, including type 1 and type 2 inflammation, and T helper (Th) 17 cell, regulatory T cell (Treg), innate lymphoid cell (ILC), and myeloid-derived suppressor cell (MDSC) responses, which highlight the polarization of several major immune cell types. These responses facilitate the pulmonary clearance and repair under physiological conditions. When exposure persists and overwhelms the clearance capacity, they foster the chronic progression of inflammation and development of progressive disease conditions, such as fibrosis and cancer. The pulmonary response to insoluble particulates thus demonstrates a distinctive disease process wherein non-infectious, persistent exposures stimulate the polarization of immune cells to orchestrate dynamic inflammatory and immune reactions, leading to pulmonary and pleural chronic inflammation, fibrosis, and malignancy. Despite large variations in particles and their associated disease outcomes, the early response to inhaled particles often follows a common path. The initial reactions entail a barrier immune response dominated by type 1 inflammation that features active phagocytosis by M1 macrophages and recruitment of neutrophils, both of which are fueled by Th1 and proinflammatory cytokines. Acute inflammation is immediately followed by resolution and tissue repair mediated through specialized pro-resolving mediators (SPMs) and type 2 cytokines and cells including M2 macrophages and Th2 lymphocytes. As many particles and fibers cannot be digested by phagocytes, resolution is often extended and incomplete, and type 2 inflammation becomes heightened, which promotes interstitial fibrosis, granuloma formation, and tumorigenesis. Recent studies also reveal the involvement of Th17-, Treg-, ILC-, and MDSC-mediated responses in the pathogenesis caused by inhaled particulates. This review synopsizes the progress in understanding the interplay between inhaled particles and the pulmonary immune functions in disease pathogenesis, with focus on particle-induced polarization of immune cells and its role in the development of chronic inflammation, fibrosis, and cancer in the lung.